Database systems for textual data: An experiment with gravestones - Rahtz, S (Oxford University Press, 1988)
This paper gives a broad view of some experiences in establishing a database of gravestones on computer, it describes the problems of having to transfer records between a number of different computers which demonstrate some interesting points about database software, secondly, some of the broader issues relating to the integration of textual, art-histoncal and archaeological data seem of importance to the future of 'literary' computing as a stand-alone discipline The paper is divided into two parts firstly, the various database systems that have been employed are described, and secondly, the question of national themes in the inscriptions, and their relationship to art-historical forms, is discussed. Examples are drawn from a study of the Protestant Cemetery in Rome, last resting place of many famous visitors to Rome since the mid 18th century, and the focus of an archaeological study since 1980, under the aegis of the Unione degli lstituti dt Arceologta, Storia e Storia dell'Arte © 1988 Oxford University Press.